High-performance wear-resistant liquid crystal polyamide-imide resin based on bio-based aliphatic amine as well as preparation and application of high-performance wear-resistant liquid crystal polyamide-imide resin
By preparing liquid crystal polyamide-imide resin based on bio-based fatty amines under high temperature and high pressure conditions, combined with vacuum viscosity-enhancing process, the problem of degradation of existing resins in high temperature environments is solved, and the development of high-performance wear-resistant resins is realized, suitable for industrial equipment under high load and high temperature environments.
Patent Information
- Application Number
- CN202411626305.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
Existing wear-resistant resins are difficult to maintain performance under high load, high friction and high temperature environments, resulting in device failure and unable to meet the high-performance needs of industrial equipment.
A liquid crystal polyamide-imide resin based on bio-based fatty amines is prepared under high temperature and high pressure conditions through salt formation reaction and prepolymerization steps. Combined with a vacuum viscosity enhancing process, a resin with excellent mechanical properties and heat resistance is obtained.
The resin material exhibits good wear resistance in high temperature environments, can meet the needs of mechanical components in the fields of aerospace, transportation, electronics and electrical appliances, and extends the service life of the device.
Smart Images

Figure CN119570030A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of resins, and particularly relates to a high-performance wear-resistant liquid crystal polyamide-imide resin based on bio-based fatty amines, and a preparation method and application thereof. Background Art
[0002] With the development of industrial equipment and manufacturing technology, polymer resins play an indispensable role in key components and equipment due to their excellent processing performance, light weight and high strength. In high-load and high-friction application scenarios, the use of wear-resistant resins has become the key to ensuring the continuous and stable operation of equipment. However, as the use environment requirements of wear-resistant resin devices gradually increase, resin materials are usually difficult to withstand their extreme conditions, which leads to device failure. Therefore, it is urgent to develop new high-performance wear-resistant resins to meet the relevant needs of industrial production.
[0003] CN202210783760.9 discloses an epoxy resin composite material and a preparation method thereof, wherein an epoxy resin prepolymer is blended with a modification aid and then cured at different temperatures to obtain an epoxy resin composite material having both good impact resistance and friction resistance. However, the molding process of such composite materials is relatively complicated and cannot be reshaped, and epoxy resin is difficult to meet the needs of a higher temperature use environment, which limits its further application. Therefore, the development of high-performance wear-resistant resins that can be used in high temperature environments is an important topic. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-performance wear-resistant liquid crystal polyamide-imide resin based on bio-based fatty amines and the preparation and application thereof.
[0005] The present invention provides a polyamide-imide, characterized in that the polyamide-imide has a general structural formula:
[0006]
[0007] Wherein R1 and R2 are selected from (CH2) m ; a+b+c=1, 0.05≤a≤0.45, b=0.5, 0.05≤c≤0.45; n≥15, m≥3;
[0008] Preferably, m=3-20.
[0009] Preferably, the polyamide-imide comprises:
[0010]
[0011]
[0012] Wherein a+b+c=1, 0.05≤a≤0.45, b=0.5, 0.05≤c≤0.45; n≥15.
[0013] The present invention provides a method for preparing polyamide-imide, comprising:
[0014] The solvent, catalyst, terephthalic acid, imide diacid and bio-based fatty amine are mixed to carry out salt-forming reaction, and then the temperature is continued to be raised to carry out prepolymerization reaction. After vacuuming to remove small molecular by-products, vacuum viscosity enhancement is carried out to obtain polyamide-imide.
[0015] Preferably, the solvent is water; the bio-based fatty amine includes one of diamine, pentanediamine and decanediamine; and the catalyst includes one of phosphoric acid, boric acid and sodium hypophosphite.
[0016] Preferably, the mass of the solvent is 40-70% of the mass of the monomers (terephthalic acid, imidic acid, bio-based fatty amine); the mass of the catalyst is 0.1%-0.5% of the total mass of the monomers (terephthalic acid, imidic acid, bio-based fatty amine); the molar ratio of terephthalic acid, imidic acid, and bio-based fatty amine is 5-45:5-45:50.
[0017] After the solvent, catalyst, terephthalic acid, imide diacid and bio-based fatty amine are mixed, the reactor is three-way connected and three-way discharged in a protective gas atmosphere (such as nitrogen atmosphere) to remove the internal air.
[0018] Preferably, the salt-forming reaction comprises: heating to 120-150° C. and reacting for 1 to 2 hours under protective gas conditions.
[0019] Preferably, the prepolymerization reaction comprises: under protective gas conditions, heating to 260-300°C at a rate of 0.8-1.2°C / min for prepolymerization reaction, maintaining the pressure in the reaction container at 1-2MPa during the heating process, and the prepolymerization reaction time is 1-2h.
[0020] Preferably, the vacuuming is performed by turning on a vacuum pump to reduce the pressure in the reaction container to -0.01 to -0.1 MPa, and maintaining the negative pressure for 30 to 60 minutes to remove by-products in the system.
[0021] Furthermore, after the small molecule by-products are removed by vacuuming, vacuum viscosity enhancement is performed after drying.
[0022] Preferably, the vacuum viscosity increasing treatment is as follows: the temperature of the heating zone of the twin-screw extruder is set to 280-320° C., the vacuum degree is set to -0.05-0.1 MPa, and the negative pressure is maintained for 30-60 min.
[0023] The protective gas is one of nitrogen and inert gas.
[0024] Preferably, the imide diacid is prepared by high-temperature reflux reaction of raw materials containing trimellitic anhydride, bio-based diamine, and a solvent, and then dried; wherein the solvent is acetic acid.
[0025] The general structural formula of the imide diacid is:
[0026] Where m≥3.
[0027] Furthermore, the structural formula of the imide diacid is:
[0028]
[0029] At least one of .
[0030] Preferably, the preparation of the imide diacid includes: obtaining it by reaction with raw materials containing trimellitic anhydride and bio-based diamine; wherein the bio-based diamine monomer is one or more of butanediamine, pentamethylenediamine, and decanediamine; the molar ratio of trimellitic anhydride to the bio-based diamine monomer is 1 to 2:1; the reaction is condensed and refluxed for 1 to 3 hours, wherein the condensation and reflux temperature is 120 to 160°C.
[0031] Furthermore, the preparation of the imide diacid includes: mixing trimellitic anhydride with a solvent, stirring and heating to 80-160° C., adding bio-based diamine after the trimellitic anhydride is completely dissolved in the solvent, condensing and refluxing for 1-3 hours, purifying, and drying to obtain the imide diacid.
[0032] The amount of the solvent is 1-6 times the total mass of the monomer feed; the solvent is acetic acid; the purification comprises: after the reaction is completed, the reactant solution is cooled to room temperature, the solvent is removed by suction filtration, and the suction filtration product is washed with ethanol solvent.
[0033] The present invention provides a wear-resistant material, which comprises the polyamide-imide.
[0034] The present invention provides an application of the polyamide-imide and the wear-resistant material in mechanical equipment in the fields of aerospace, transportation, and electronic appliances, such as mechanical gaskets, wear-resistant bearings, self-lubricating components and other mechanical parts.
[0035] The present invention preliminarily develops an imide diacid monomer by combining bio-based fatty amine and trimellitic anhydride, feeds imide diacid, terephthalic acid and bio-based fatty amine in a certain molar ratio, performs a salt-forming-prepolymerization step under high temperature and high pressure conditions, and performs vacuum viscosity enhancement in a twin screw to obtain a liquid crystal polyamide-imide resin. The obtained resin material has excellent mechanical properties and heat resistance, and also exhibits excellent wear resistance, and has broad application prospects in the fields of aerospace, transportation, electronic appliances, etc., and can be used to prepare mechanical parts such as wear-resistant bearings, self-lubricating components, and mechanical gaskets.
[0036] Beneficial Effects
[0037] (1) Compared with traditional thermosetting wear-resistant resins, the liquid crystal polyamide-imide of the present invention is a type of high-performance thermoplastic resin that can be processed in a variety of molding methods and has a wide range of application scenarios, effectively avoiding the limitations of the curing process on molding processing. (2) Compared with traditional wear-resistant resins that are difficult to meet the requirements of working in extreme environments, the high-performance wear-resistant resin developed by the present invention has good heat resistance, chemical solvent resistance and friction resistance, and can meet the requirements of industrial equipment for resin performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 are micrographs of the liquid crystal phases of Examples 1 and 2;
[0039] Figure 2 The thermogravimetric curves of the embodiments and the comparative examples are shown;
[0040] Figure 3 The friction scratch morphology of Examples 1 (left) and 2 (right) are shown. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] The sources and specifications of the raw materials and reagents used in the experiment are shown in Table 1:
[0043] Table 1 Experimental materials and reagents
[0044] name Specification factory Trimellitic anhydride 99% Shanghai MacLean Biochemical Technology Co., Ltd. Butanediamine 99% Beijing Bailingwei Technology Co., Ltd. Terephthalic acid 99% Hengyi Petrochemical Co., Ltd. Sodium Hypophosphite 99% Shanghai Titan Technology acetic acid 99% Shanghai MacLean Biochemical Technology Co., Ltd.
[0045] Example 1
[0046] In this embodiment, a bio-based liquid crystal polyamide-imide material is prepared by the following method:
[0047] Add acetic acid (729.6 g) and trimellitic anhydride (384.2 g) into a three-necked flask. Heat at 120°C until the solution is clear, add pentamethylenediamine (102.2 g), and reflux at 140°C for 1 h. Cool the reactants to 25°C, remove the acetic acid by suction, and wash with ethanol until there is no sour smell, and dry in an oven (80°C, 24 h) to obtain imide diacid monomer powder.
[0048] In a 2L reactor, pentamethylenediamine (2 mol, 204.36 g), terephthalic acid (0.2 mol, 33.23 g), imide diacid (1.8 mol, 936.97 g), deionized water (821 mL) and sodium hypophosphite (1.18 g) were added respectively, and then the reactor was three-way and three-way discharged with nitrogen to exclude the internal air. The reactor was heated to 120°C for 1 hour for salt formation reaction. After the salt formation reaction was completed, the temperature was raised to 260°C at a heating rate of 1.2°C / min for prepolymerization, and the pressure in the reactor was maintained at 1 MPa during the heating process. After 2 hours of prepolymerization, the vacuum pump was turned on to gradually reduce the pressure in the reactor to -0.1 MPa, and the negative pressure state was maintained for 30 minutes to exclude small molecules in the system. After the reaction was completed, nitrogen was introduced into the reactor to control the pressure in the reactor to reach normal pressure, and the discharge valve was opened to obtain a liquid crystal polyamide-imide polymer (the structure is shown in the figure below). The obtained liquid crystal polyamide-imide polymer was dried, and the temperature of the heating zone of the twin-screw extruder was set to 320° C. and the vacuum degree was -0.05 MPa, and the liquid crystal polyamide-imide polymer (structure as shown in the figure below) was vacuum-thickened.
[0049]
[0050] Imidodiacid structure
[0051]
[0052] Liquid crystal polyamide-imide structure
[0053] Example 2
[0054] This embodiment prepares bio-based liquid crystal polyamide-imide material, and the method is as follows: The preparation method of imide diacid is the same as that of Example 1. Then, pentamethylenediamine (2 mol, 204.36 g), terephthalic acid (1.8 mol, 299.04 g), imide diacid (0.2 mol, 104.11 g), deionized water (424 mL) and sodium hypophosphite (0.61 g) were added to a 2L reactor, and then the reactor was three-way and three-way released with nitrogen to exclude the internal air. The reactor was heated to 120°C and continued for 1 hour for salt formation reaction. After the salt formation reaction was completed, the temperature was raised to 260°C at a heating rate of 1.2°C / min for prepolymerization, and the pressure in the reactor was maintained at 1MPa during the heating process. After 2 hours of prepolymerization, the vacuum pump was turned on to gradually reduce the pressure in the reactor to -0.1MPa, and the negative pressure state was maintained for 30 minutes to exclude small molecules in the system. After the reaction is completed, nitrogen is introduced into the reactor, the pressure in the reactor is controlled to reach normal pressure, and the discharge valve is opened to obtain a liquid crystal polyamide-imide polymer (the structure is shown in the figure below). The obtained liquid crystal polyamide-imide polymer is dried, and the temperature of the heating zone of the twin-screw extruder is set to 320°C and the vacuum degree is -0.05MPa, and the liquid crystal polyamide-imide polymer is vacuum-thickened.
[0055]
[0056] Liquid crystal polyamide-imide structure
[0057] Comparative Example 1
[0058] This comparative example prepares a semi-aromatic polyamide for comparison with Examples 1 to 2, and the method is as follows: add pentamethylenediamine (2 mol, 204.36 g), terephthalic acid (1 mol, 166.13 g), isophthalic acid (1 mol, 166.13 g), deionized water (375 mL) and sodium hypophosphite (0.53 g) into a 2L reactor, and then use nitrogen to perform three passes and three releases on the reactor to exclude the internal air. The reactor is heated to 120°C for 1 hour to perform the salt-forming reaction. After the salt-forming reaction is completed, the temperature is raised to 260°C at a heating rate of 1.2°C / min for prepolymerization, and the pressure in the reactor is maintained at 1 MPa during the heating process. After 2 hours of prepolymerization, turn on the vacuum pump to gradually reduce the pressure in the reactor to -0.1 MPa, maintain the negative pressure state for 30 minutes, and exclude small molecules in the system. After the reaction is completed, nitrogen is introduced into the reactor, the pressure in the reactor is controlled to reach normal pressure, and the discharge valve is opened to obtain a liquid crystal polyamide-imide polymer (the structure is shown in the figure below). The obtained semi-aromatic polyamide is dried, and the temperature of the heating zone of the twin-screw extruder is set to 320°C and the vacuum degree is -0.05MPa to vacuum-thicken the semi-aromatic polyamide.
[0059]
[0060] Semi-aromatic polyamide structure
[0061] The performance of Examples 1 to 2 and Comparative Example 1 was tested
[0062] 1) Hot stage polarizing microscope (POM)
[0063] The test procedure is: the heating stage is heated from 30°C to 350°C at a heating rate of 20°C / min to determine the liquid crystal phase transition temperature of the polymer.
[0064] 2) Thermogravimetric analysis test (TGA)
[0065] The test procedure is: the temperature is raised from 30℃ to 600℃ at a heating rate of 10℃ / min, and the thermal weight loss behavior of the polymer during this process is studied. The temperature corresponding to 5% weight loss is taken as the thermal decomposition temperature (T d,5% ).
[0066] 3) Heat deformation temperature test
[0067] The test procedure is as follows: a rectangular specimen is placed in an oil bath, the oil bath temperature is increased at a heating rate of 120°C / h, and the temperature when the specimen deflection reaches the standard deflection is recorded, which is the heat deformation temperature.
[0068] 4) Friction scratch test
[0069] The test procedure is as follows: the cone-shaped diamond stylus has a 120° apex angle and a 200μm tip radius. The sample is fixed on a rotating sample stage and the scratch test is performed at a normal force of 2N and a sliding speed of 1mm / s.
[0070] The phase transition temperature of the liquid crystal was characterized by a hot stage polarizing microscope at a heating / cooling rate of 30°C / min for Examples 1-2 and Comparative Example 1, as shown in Table 2. Figure 1 The polyamide-imide obtained in Examples 1 to 2 enters the liquid crystal phase at about 290-312° C., and the melt viscosity drops sharply. At this time, it has good processing performance and can meet subsequent processing requirements.
[0071] According to the thermal gravimetric test and thermal deformation test of Examples 1 to 2 and Comparative Example 1, see Table 2 and Figure 2 : T of the semi-aromatic polyamide obtained in Comparative Example 1 d,5% Reached 438 ℃; Examples 1 ~ 2 obtained liquid crystal copolyester compared with Comparative Example 1, the thermal decomposition temperature (T d,5% ) is even better, indicating that bio-based polyamide-imide has good thermal stability. At the same time, Examples 1 to 2 show excellent resistance to thermal deformation, and the thermal deformation temperature is all >200°C, which can meet the use requirements in high temperature environments.
[0072] The friction scratch test was performed on Example 2. Figure 3 According to the microscopic morphology of the scratches, it can be found that there are only a small amount of debris at the resin scratches corresponding to Examples 1 and 2, and the scratch depth (6-17 μm) and the scratch width (338-420 μm) are not obvious, indicating that it has excellent friction resistance.
[0073] Table 2 Physical properties of Examples 1 to 2 and Comparative Example 1
[0074]
Claims
1. A polyamide-imide, characterized in that The polyamide-imide general structure formula: Wherein R1 and R2 are selected from (CH2) m ; a+b+c=1, 0.05≤a≤0.45, b=0.5, 0.05≤c≤0.45; n≥15.
2. The polyamide-imide according to claim 1, characterized in that: The m≥3.
3. The polyamide-imide according to claim 1, characterized in that: The polyamide-imide comprises: Wherein a+b+c=1, 0.05≤a≤0.45, b=0.5, 0.05≤c≤0.45; n≥15.
4. A method for preparing a polyamide-imide, comprising: The solvent, catalyst, terephthalic acid, imide diacid and bio-based fatty amine are mixed to carry out salt-forming reaction, and then the temperature is continued to be raised to carry out prepolymerization reaction, vacuum is drawn, and vacuum viscosity is increased to obtain polyamide-imide.
5. The preparation method according to claim 4, characterized in that: The solvent is water; the catalyst includes one of phosphoric acid, boric acid, and sodium hypophosphite; the bio-based fatty amine includes one of butanediamine, pentamethylenediamine, and decanediamine; The imide diacid structural formula comprises: Where m≥3.
6. The preparation method according to claim 4, characterized in that: The mass of the solvent is 40-70% of the total mass of the monomers; the mass of the catalyst is 0.1%-0.5% of the total mass of the monomers; and the molar ratio of terephthalic acid, imide diacid and bio-based fatty amine is 5-45:5-45:
50.
7. The preparation method according to claim 4, characterized in that: The salt-forming reaction comprises: heating to 120-150° C. under protective gas conditions and reacting for 1-2 hours; the prepolymerization reaction comprises: heating to 260-300° C. at a heating rate of 0.8-1.2° C. / min under protective gas conditions and reacting, maintaining the pressure in the reaction container at 1-2 MPa during the heating process, and the prepolymerization reaction time is 1-2 hours.
8. The preparation method according to claim 4, characterized in that: The vacuum pumping: Turn on the vacuum pump to reduce the pressure in the reaction container to -0.01 to -0.1 MPa, maintain the negative pressure for 30 to 60 minutes, and remove by-products in the system; The vacuum viscosity increasing treatment: the temperature of the heating zone of the twin-screw extruder is set to 280-320° C., and the vacuum degree is set to -0.05--0.1 MPa.
9. A wear-resistant material, characterized in that: The wear-resistant material comprises the polyamide-imide resin according to claim 1.
10. Use of the polyamide-imide according to claim 1 and the wear-resistant material according to claim 9 in the fields of aerospace, transportation, and electronic appliances.
Citation Information
Patent Citations
An epoxy resin composite material and its preparation method
CN115216119B
Liquid-crystal polyamide imide and preparation method therefor
CN105237767A
Preparation method of polyimide modified nylon resin
CN106336512A
Novel poly(amide-imide) resins using aromaticdicarboxylic acid and preparation method thereof
KR1020030018859A
Novel polyamideimides and preparation and compositions comprised thereof
US20110160407A1